Treadmill Exercise Improves Motor Function by Suppressing Purkinje Cell Loss in Parkinson Disease Rats - Lee, Jae-Min (Int Neurourol J, 2018)
PURPOSE: Rotenone is the most widely used neurotoxin for the making Parkinson disease (PD) animal model. The neurodegenerative disorder PD shows symptoms, such as slowness of movements, tremor at resting, rigidity, disturbance of gait, and instability of posture. We investigated whether treadmill running improves motor ability using rotenone-caused PD rats. The effect of treadmill running on PD was also assessed in relation with apoptosis of cerebellar Purkinje cells. METHODS: Treadmill running was applied to the rats in the exercise groups for 30 minutes once a day for 4 weeks, starting 4 weeks after birth. We used rota-rod test for the determination of motor coordination and balance. In this experiment, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining, immunohistochemistry for calbindin, glial fibrillary acidic protein (GFAP), Iba-1, and western blot analysis for Bax and Bcl-2 were performed. RESULTS: Treadmill running enhanced motor balance and coordination by preventing the loss of Purkinje cells in the cerebellar vermis. Treadmill running suppressed PD-induced expression of GFAP-positive reactive astrocytes and Iba-1-positive microglia, showing that treadmill running suppressed reactive astrogliosis and microglia activation. Treadmill running suppressed TUNEL-positive cell number and Bax expression and enhanced Bcl-2 expression, demonstrating that treadmill running inhibited the progress of apoptosis in the cerebellum of rotenone-induced PD rats. CONCLUSIONS: Treadmill running improved motor ability of the rotenone-induced PD rats by inhibiting apoptosis in the cerebellum. Apoptosis suppressing effect of treadmill running on rotenone-induced PD was achieved via suppression of reactive astrocyte and inhibition of microglial activation.